How technology Is reshaping financial services: Essays on consumer behavior in card, channel and cryptocurrency services - GENG, Dan (Institutional Knowledge at Singapore Management University, 2017)
The financial services sector has seen dramatic technological innovations in the last several years associated with the “fintech revolution.” Major changes have taken place in channel management, credit card rewards marketing, cryptocurren-cy, and wealth management, and have influenced consumers’ banking behavior in different ways. As a consequence, there has been a growing demand for banks to rethink their business models and operations to adapt to changing consumer be-havior and counter the competitive pressure from other banks and non-bank play-ers. In this dissertation, I study consumer behavior related to different aspects of financial innovation by addressing research questions that are motivated by theo-ry-focused research literature and managerial considerations in business practice. I seek to understand how technology is reshaping financial services, and how finan-cial institutions can leverage big data analytics to create deep insights about con-sumer behavior for decision support. The first essay studies credit card-based partnerships between banks and re-tailers. I test a number of hypotheses that assess the indirect effects related to the impacts of credit card programs in my research setting. I use publicly-available data, together with proprietary data from a large financial institution, to examine the impact of card-based promotions on consumer behavior and merchant perfor-mance. The results show that such promotions create positive indirect effects, leading to increased purchases from customers of other banks, in addition to the bank running the promotion. This research creates insights that banks can leverage to optimize their card-based reward programs, and paves the way forward for strengthening credit card merchant partnerships. The second essay emphasizes the importance of investigating bank branch network changes, including branch openings and closures, and their impacts on customers’ omni-channel banking behavior. I find that branch openings create customer awareness and lead to synergetic increases in transactions across chan-nels, and branch closures result in a migration pattern from alternative channels to online banking due to the joint effects of negative perceptions and substitution. This essay contributes to our knowledge of multi-channel services in the IS and Management literature, and provides strategic implications on branch network re-structuring in omni-channel financial services. In the third essay, I draw on social contagion theory and a spatiotemporal per-spective to explore the global penetration of bitcoin, and how security events have been influential in this process. This essay uses transaction data from Mt.Gox, one of the largest bitcoin exchange platforms in the world before its bankruptcy in 2014, and other publicly-available data sources for county-level information. The results suggest that the global penetration of bitcoin is jointly influenced by the economy, technology and regulatory situation of a country. And news about the occurrence of security incidents related to the cryptocurrency has a negative im-pact on its cross-country diffusion. This study contributes to the literature on the diffusion of emerging financial technologies, as well as business practices at the early stage of the development of a digital currency.